Effects of PrPC on DF‐1 cells' biological processes and RNA‐seq‐based analysis of differential genes. Issue 10 (9th May 2018) - Zhang, Tian‐liang; Wan, Xue‐rui; Wu, Run; Wang, Chuan
Abstract : To reveal the effects of PrP C on cells' biological processes and on gene expression. We established stable DF‐1 (PrP C ‐knockdown (KD)) cells, and combined with DF‐1 (wt) and DF‐1 (PrP C ‐overexpression (OE)) cells that we previously established we studied the effects of chicken PrP C (PrP C ) on DF‐1 cells' processes. Then by using high throughput sequencing technology (HTS) and bioinformatics, we analyzed the differentially expressed genes (DEGs) between these cells. The results show that compared with DF‐1 (wt) and DF‐1 (PrP C ‐scramble), DF‐1 (PrP C –KD) are significantly decreased in adhesion, proliferation, formation rate of colony and cells number of colony, scratch wound healing rate, cells number of invasion and migration, S phase cell populations, but the apoptosis rate and G1 phase cell populations are significantly increased. Conversely, all of these features in DF‐1 (PrP C ‐OE) are opposite. In addition, compared with DF‐1 (wt), we found that there are totally 1055 DE genes between DF‐1 (PrP C –KD) and DF‐1 (PrP C ‐OE) cells. After Go and pathway enrichment analysis, we know that these DEGs are significantly enriched in cell, cell part, cellular process, and metabolic pathway. In short, we found that PrP C can promote DF‐1 cells' processes except apoptosis. Furthermore, PrP C involves in the focal adhesion, cancer, ribosome, metabolic pathways, and so forth, and the overexpression of PrP C can promote the pathway of amoebiasis, but its down‐regulation can promote the pathway of serotonergic synapse. However, the details are keeping unknown and that would be our next research. Abstract : Based on several stable DF‐1 cell lines, we studied the effects of chicken PrP C (PrP C ) on DF‐1 cells' processes. And then by using high throughput sequencing technology (HTS) and bioinformatics, we analyzed the differentially expressed genes (DEGs) between these cells. The results show that PrP C can promote DF‐1 cells' processes except apoptosis; PrP C involves in the focal adhesion, cancer, ribosome, metabolic pathways and so forth, and the overexpression of PrP C can promote the pathway of amoebiasis, but its down‐regulation can promote the pathway of serotonergic synapse.